2019
DOI: 10.1002/ppul.24413
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist versus conventional ventilation in the pediatric population: Are there benefits?

Abstract: Introduction Neurally‐adjusted ventilator assist (NAVA) is a relatively new form of ventilation in which the electrical activity of the diaphragm is sensed by a catheter. The amplitude of this electrical signal is then used to deliver an appropriately proportioned pressure supported breath to the patient. Due to the synchronous nature of the breaths and the patient‐adjusted nature of the support, NAVA has been shown to have benefits over conventional ventilation. Meta‐analyses were conducted of published pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
4
9
1
Order By: Relevance
“…Our results confirm that NAVA significantly reduces patient-ventilator asynchrony and significantly increases oxygenation compared to conventional assisted mechanical ventilation [37]. In fact, in our study, the better synchrony with NAVA was confirmed by a significantly longer Time sync and substantially better Time sync /Ti neu.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our results confirm that NAVA significantly reduces patient-ventilator asynchrony and significantly increases oxygenation compared to conventional assisted mechanical ventilation [37]. In fact, in our study, the better synchrony with NAVA was confirmed by a significantly longer Time sync and substantially better Time sync /Ti neu.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies [14,37] highlighted the positive effect of NAVA on PaO 2 /FiO 2 ratio, but they did not show significant effects on PaCO 2 as reported in our study, probably due to the recovery of a normalized respiratory pattern with normocapnia in patients recovering from PARDS.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Karikari et al 47 performed a meta-analysis of published pediatric studies to compare ventilatory end points between NAVA and conventional ventilation. Asynchrony was 17% lower, peak inspiratory pressure was 2 cm H 2 O lower, and S pO 2 was 1% greater with NAVA.…”
Section: Modes For Improving Synchronymentioning
confidence: 99%